1989
DOI: 10.1002/ijc.2910440410
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control investigation of cancer of the oral tongue and the floor of the mouth in Southern India

Abstract: A case-control study of cancer of the oral tongue and floor of mouth was conducted in Kerala, Southern India, on 228 cases and 453 hospital-based controls, matched for age, sex and religion. We studied pan(betel)-tobacco-chewing, bidi (local type of cigarette)-and-cigarette-smoking, alcohol-drinking and snuff use, for their associations with risk, in males. Among females, only pan-tobacco-chewing was analyzed, as very few females indulged in the other habits. In males, a significantly increased risk was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
1
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 10 publications
(6 reference statements)
6
86
1
4
Order By: Relevance
“…It is further confirmed by multivariate analysis, which shows that education, particularly low education, occupation, agriculture and blue collar and low monthly household income were the significant independent risk factors. These findings are consistent with the similar studies done in the other parts of India by Chattopadhyay (1989); Sankaranarayanan et al (1989) and Rao et al (1994) reported earlier.…”
Section: Discussionsupporting
confidence: 93%
“…It is further confirmed by multivariate analysis, which shows that education, particularly low education, occupation, agriculture and blue collar and low monthly household income were the significant independent risk factors. These findings are consistent with the similar studies done in the other parts of India by Chattopadhyay (1989); Sankaranarayanan et al (1989) and Rao et al (1994) reported earlier.…”
Section: Discussionsupporting
confidence: 93%
“…Tobacco chewing and smoking have been identified as the major risk factors for these cancers in India. 15,[17][18][19] Cancers of the oral cavity occupy the second-highest position among males in Kolkata. The prevalent chewing habits involve use of betel quid (betel leaf with tobacco, areca nut, lime), gutkha (dried mixture of betel quid and tobacco sold in attractive pouches), mawa and zarda (flavoured tobacco) or khaini (crude form of dried ground tobacco with lime).…”
Section: Discussionmentioning
confidence: 99%
“…Although alcohol can be considered an independent risk factor, fifteen cases reported to be regular alcohol drinkers, while ten cases were occasional drinkers. Some studies have reported a higher prevalence of OL among alcohol users in each age group, as well as in each tobacco habit category (15,19), but alcohol consumption showed no independent association with OL in other research publications (4,10). The susceptible age for leukoplakia lesions ranged from 40 to 70 years in a study from the Netherlands.…”
Section: Discussionmentioning
confidence: 89%
“…Although alcohol is a risk factor for oral cancer, (19) it is not an established risk factor for OL (4,10). The clinical records used for patient characterization in the current study did not contain consistent information on alcohol use; thus, we were unable to evaluate the possible importance of this factor for our patients.…”
Section: Discussionmentioning
confidence: 91%